METHODS OF STUDYING THE ECOSTABILIZED NATURAL ENVIRONMENT IN THE REPUBLIC OF KARAKALPAKSTAN (on the example of soil) - Kilichov, Orifjon Alisherovich (SCIENCE and SOCIETY, 2026)
In this article, the current geoecological state of the dried bottom of the Aral Sea, the work carried out in the scientific direction on the analysis of changes in relief forms, as well as the study of changes occurring in landscapes, the structure of the earth’s surface and the formed layers are presented. The results of research conducted on the dried-up part of the Aral Sea were analyzed.
Keywords: Aral Sea; salinity; geoecology; landscape; section; stratum; soil composition; humus; nutrients